2020
DOI: 10.1111/1475-4932.12530
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Transmission of Body Mass and Obesity Status in Australia

Abstract: We estimate the intergenerational transmission of the body‐mass index (BMI) and obesity status using the Household, Income and Labour Dynamics in Australia Survey. The intergenerational elasticity of BMI between mother and adolescent is 0.242, which is consistent with estimates from other countries. Controlling for adolescent‐specific fixed effects reduces the estimated elasticity to 0.043. This suggests that genetics and the permanent environment may explain much of the observed persistence of BMI across gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…Other research has focused on the transmission of educational (dis)advantage from grandparents and parents to children (Hancock et al, 2018), the transmission of health outcomes across generations (Huang, 2020;James et al, 2020), the transmission of attitudes , joblessness (Curry et al, 2019), and the transmission of wealth (Lersch & Baxter, 2020). In sum, there is clear evidence of intergenerational associations which show that the playing field is not level for all children and that if we are to fully understand and address social and economic disadvantage in Australia, we need to understand not only the life course journeys of individuals, but also their family background.…”
Section: Life Course Approaches and Intergenerational Inequality In A...mentioning
confidence: 99%
“…Other research has focused on the transmission of educational (dis)advantage from grandparents and parents to children (Hancock et al, 2018), the transmission of health outcomes across generations (Huang, 2020;James et al, 2020), the transmission of attitudes , joblessness (Curry et al, 2019), and the transmission of wealth (Lersch & Baxter, 2020). In sum, there is clear evidence of intergenerational associations which show that the playing field is not level for all children and that if we are to fully understand and address social and economic disadvantage in Australia, we need to understand not only the life course journeys of individuals, but also their family background.…”
Section: Life Course Approaches and Intergenerational Inequality In A...mentioning
confidence: 99%
“…Los estudios han explorado la magnitud y direccionalidad de la correlación de los indicadores utilizados para definir obesidad y riesgo cardiovascular, el Índice de Masa Corporal (IMC) y la Circunferencia de Cintura (CC) de los padres con la (6,7) de sus hijos . Los resultados muestran que cuando los indicadores se encuentran aumentados en los progenitores, es probable que se encuentren (8,9) aumentados en la descendencia .…”
Section: Introductionunclassified
“…While national policies are now prioritizing the prevention of obesity across the population [5], people with obesity are likely to comprise a significant proportion of the inpatient population for some time to come. Recent data indicates that 63% of the Australian adult population meets the criteria for obesity or overweight, which is the fifth highest prevalence amongst Organisation for Economic Cooperation and Development (OECD) member countries [6]. International research has confirmed that inpatients with obesity are more likely to experience lower quality care, increased length of stay and adverse events such as the development of pneumonia, infection, falls, and pressure injuries [7].…”
Section: Introductionmentioning
confidence: 99%